The democratic faith : essays on democratic citizenship - Sniderman, Paul M. (Castle lectures in ethics, politics, and economics., 2017)
Can the citizens of a democracy be trusted to run it properly? Modern political science has concentrated on cataloguing voters' failings-their lack of knowledge, tolerance, or consistency in political thinking. While it would be a mistake to think this portrait of citizens is simply wrong, it is a deeper mistake to accept it as a satisfactory likeness. In this book, Paul Sniderman demonstrates that a concentration on the pathologies of citizens' political thinking has obscured the intense clash of opposing belief systems in the electorate. He shows how a concentration on racism has distorted u.